Reporting to the Police Among People with Mental Illnesses Who Were Victims of Violence - Bergdolt, Juliane (Victims & offenders, 2024)
The aim of this study was to explore reporting to the police in people with mental illnesses who were victims of violence. Fifty-eight persons with mental illnesses who had experienced physical, sexual, or psychological violence in the past three years answered quantitative questionnaires. After victimization, 33 (56.9%) participants had police contact, with 22 of them having initiated this contact. Participants who were younger (p = .027), had a substance use disorder (25.8% vs. 50.0%), used drugs or alcohol during victimization (25.0% vs. 51.7%), or experienced shame or guilt (27.5% vs. 62.5%) after victimization were less likely to report to the police. The most frequently named reasons not to report were fear of secondary victimization by the police and the belief that the police could not do anything or that the perpetrator would not be punished adequately.